SISTEM AKUNTANSI PENGELUARAN KAS PADA PT. JASA RAHARJA LOKET KANTOR CABANG SUMATERA UTARA - Sihombing, Elisa; Sijabat, Jadongan; Berliana Lumban Gaol, Manatap (Universitas HKBP Nommensen, 2022)
The purpose of this study is to determine the application of the system, accounting for cash distribution at PT. PT. Jasa Raharaja Loket Kantor Cabang Sumatera Utara. The type of research used is the Qualitative method. The data used in this study is Premier data. Data collection techniques used in this study are interviews, documentation related to cash expenditure. Metode analisis data yang digunakan dalam penelitian ini yaitu metode analiss deskriptif dan komperatif. The results showed that the cash disbursement accounting system at PT. Jasa Raharja Kantor Cabang Sumatra Utara counter is carried out through interbank transfer. The documents used are payment receipts, payment approvals, transfer orders and cash out proofs. Related functions are functions that require cash expenditure, cashiers, and branch office heads.